LIQUIDITY, SOLVENCY AND PROFITABILITY ANALYSIS COMPANIES BEFORE AND AFTER ACQUISITION - -, Suci Andriani; Marzuki; Chairil Akhyar; Adnan (PT. Radja Intercontinental Publishing, 2023)
This study aims to analyze the Liquidity, Solvency and Profitability of the company before and after the acquisition. This research uses secondary data in the form of annual financial statements of companies listed on the Indonesia Stock Exchange in 2012-2020. The number of companies in this study is 33 companies with sampling using purposive sampling techniques with certain criteria in accordance with the research objectives. The data analysis methods used in this study are descriptive statistical methods and normality tests. Test the hypothesis in this study using the Wilcoxon Signed Rank Test. The results of this study show that the Liquidity ratio, namely Current Ratio (CR) and Quick Ratio (QR) and Solvency ratio, namely Debt to Equity Ratio (DER) and Debt to Assets Ratio (DAR) show that there is no significant difference before and after the acquisition. Then the Profitability ratio, namely Return on Equity (ROE) and Return on Assets (ROA) shows that there is a significant difference before and after the acquisition, but the difference actually shows a significant decline in the company's financial performance after the acquisition.